NIAT BERALIH PENGGUNAAN SMARTPHONE: MENGINTEGRASIKAN KERANGKA KERJA DORONG-TARIK-TAMBAT - Muhamad Syaeful Anwar; Lely Afiati (JURNAL LENTERA BISNIS, 2024)
This study empirically examines and analyzes the factors influencing the switching intention usage of Android smartphone to iOS smartphone. The research investigates three main categories: push factors, pull factors, and mooring factor. Push factors include dissatisfaction and low quality. Pull factors include alternative attractiveness and perceived usefulness. Mooring factor include switching costs. The research design employs an explanatory approach to determine one or more variables that explain the cause-and-effect relationship with other variables. Data was collected through a survey using Google Form with 123 respondents. Data analysis was conducted using SPSS software to analyze respondents characterstics and SmartPLS software to analyze the measurement model and structural model. The results show that push and pull factors positively and significantly affect switching intention. Switching costs moderate the influence of pull factors on switching intention of smartphone usage while, switching costs do not moderate the influence of push factors on switching intention of smartphone usage.